Attachment orientation and dynamics of negative and positive emotions in daily life - Tammilehto Jaakko; Kuppens Peter; Bosmans Guy; Flykt Marjo; Peltonen Kirsi; Vänskä Mervi; Lindblom Jallu (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
People's attachment orientation contributes to their emotional experiences. However, the associations between attachment orientation and emotion dynamic features have remained unclear. In this preregistered study, we tested the associations of attachment orientation with baseline level, variability, inertia, and differentiation of emotions using two ecological momentary assessment adult samples (N = 122; N = 127). Attachment anxiety predicted a higher baseline level of negative emotions in both samples and a lower baseline level of positive emotions in one sample. Attachment avoidance predicted a lower baseline level of positive emotions in both samples. After covarying baseline level, no associations of attachment orientation were detected with variability, inertia, and differentiation. Our findings suggest that attachment orientation is associated with baseline level rather than other emotion dynamic features.